Design Thinking: Creativity and Critical Thinking in College - Cecilia Latorre-Cosculluela; Sandra Vázquez-Toledo; Ana Rodríguez-Martínez; Marta Liesa-Orús (Universidad Autónoma de Baja California, 2020)
The educational model proposed by the European Higher Education Area calls for a transformation geared toward socio-constructivist learning that prepares students for globalization, technological advancement, and a capacity for constant innovation. In this regard, the design thinking methodological approach is becoming increasingly relevant in future teachers' college education. It is in this context that this study describes a design thinking experience aimed at designing an educational innovation project and uses a questionnaire to analyze 107 college students' perceptions of the process. The results show that the work teams were able to design innovative approaches to real problems they faced, becoming actively engaged in a shared search for solutions. This active methodology boosts students' confidence in their creative capacities and the development of empathic skills.